Lithium lanthanum zirconium tantalum oxide solid electrolyte with lithium tantalate composite garnet structure and preparation method of lithium lanthanum zirconium tantalum oxide solid electrolyte

By introducing lithium tantalate at the grain boundary of the solid electrolyte of garnet structure oxide, the low ion conductivity problem caused by holes and grain boundary resistance is solved, and higher density and conductivity is achieved, and the cycle stability of the battery is improved.

CN119528573AInactive Publication Date: 2025-02-28JILIN UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510104852.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing garnet structure oxide solid electrolytes are prone to generate holes and grain boundary resistance during high-temperature sintering, resulting in a low total ionic conductivity and a prone to lithium dendrites.

Method used

By introducing lithium tantalate that does not react with solid electrolyte, the density at the grain boundaries is increased, the porosity and resistance are reduced, and the ionic conductivity is improved.

Benefits of technology

It effectively improves the density and ionic conductivity of solid electrolytes, inhibits the growth of lithium dendrites, and improves the circulation stability of all-solid lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528573A_ABST
    Figure CN119528573A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure and a preparation method of the lithium lanthanum zirconium tantalum oxide solid electrolyte, and belongs to the technical field of all-solid-state lithium ion batteries. The preparation method comprises the following steps: heating lanthanum oxide, ball-milling and uniformly mixing the lanthanum oxide, lithium hydroxide monohydrate, zirconium oxide and tantalum oxide in isopropanol, and pre-sintering to obtain a precursor; and performing secondary ball milling on LiTaO3 accounting for 1-10% of the mass of the precursor and the precursor, uniformly mixing, drying, tabletting, and sintering at high temperature to obtain the solid electrolyte material. The ionic conductor LiTaO3 is introduced into the grain boundary of the lithium lanthanum zirconium tantalum oxide solid electrolyte, the porosity is reduced, the grain boundary bonding strength is enhanced, the resistance and activation energy of the electrolyte are reduced in the sintering process, lithium tantalate does not react with the garnet structure solid electrolyte, impurities hindering ion transmission are not generated, the ionic conductivity at the room temperature is improved, and the service life of the lithium lanthanum zirconium tantalum oxide solid electrolyte is prolonged. The migration activation potential barrier of lithium ions is reduced, and the problem of low total ionic conductivity caused by the grain boundary problem is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state lithium-ion batteries, and in particular relates to a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure and a preparation method thereof. Background Art

[0002] As the population increases, society's demand for energy continues to expand, and lithium-ion batteries have become a widely used energy storage device in today's society. However, traditional lithium-ion batteries mostly use organic liquid electrolytes, which may cause leakage and decomposition when the battery short-circuits and overheats, causing fires. Therefore, the development of safer and more reliable new batteries has become a focus of social attention. All-solid-state lithium metal batteries have a similar structure to traditional lithium-ion batteries, use safe and reliable solid electrolytes, and can use lithium metal negative electrodes with high energy density and high-voltage positive electrode materials. They have shown many advantages and have become a research hotspot for the next generation of new battery systems.

[0003] Garnet structure oxide solid electrolyte Li7La3Zr2O 12 (LLZO) has good mechanical properties and high room temperature ionic conductivity, and is a solid electrolyte material that has attracted much attention. However, the density of ceramic electrolyte materials is positively correlated with their ionic conductivity. Due to the inevitable pores generated during high-temperature sintering and the large grain boundary resistance between the grains, its total ionic conductivity is low and lithium dendrites are easily generated. Currently, researchers generally introduce additives to improve the grain boundary problem. Huang (ACS Appl. Mater. Interfaces. 2022, 14,40959-40996) et al. increased the density of Ta-doped LLZO (LLZTO), reduced the interface resistance, and increased the critical current density from 1.50 mA·cm by adding La2O3. -2 Increased to 2.12 mA·cm -2 However, at high temperatures, La2O3 easily reacts with LLZTO to form the impurity LaTaO4. Wang (ACS Appl. Mater. Interfaces. 2020, 12, 56118-56125) et al. improved the density of LLZO solid electrolyte by adding Al2O3, but the ionic conductivity decreased due to the formation of LiAlO2 at the grain boundaries. The reaction between the additive and the electrolyte itself makes it difficult to take into account both density and ion transport. Therefore, it is necessary to further explore new grain boundary additives that do not react with LLZO, while taking into account both density and ion transport. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to provide a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure and a preparation method thereof. The present invention introduces lithium tantalate that does not react with the solid electrolyte, thereby improving the density and solving the problem of low total ion conductivity caused by grain boundaries, so that the prepared lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure can be applied to all-solid-state lithium-ion batteries.

[0005] The method of the present invention comprises the following steps: heating lanthanum oxide, mixing it evenly with lithium hydroxide monohydrate, zirconium oxide and tantalum oxide in isopropanol by ball milling, and obtaining a precursor after pre-sintering; mixing LiTaO3 with 1-10% of the precursor mass and the precursor by secondary ball milling and drying; finally, pressing the powder into a sheet and putting it into a crucible, and obtaining it after high-temperature sintering in a muffle furnace. The present invention reduces the porosity, enhances the grain boundary bonding strength, and reduces the electrolyte resistance and activation energy during the sintering process by introducing the ion conductor LiTaO3 into the grain boundary of lithium lanthanum zirconium tantalum oxygen solid electrolyte.

[0006] The preparation method of a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure described in the present invention comprises the following steps: (1) placing lanthanum oxide in a muffle furnace and heating it to remove impurities to obtain pure lanthanum oxide powder; (2) lithium hydroxide monohydrate, lanthanum oxide, zirconium oxide and tantalum oxide heat-treated in step (1) are mixed according to the chemical formula Li 7- x Ln3Z 2-x Ta x O 12 The mixture is mixed in a molar ratio of 100 and 100 and put into a ball mill, and ball milling is performed using isopropanol as a dispersant. After the ball milling is completed, the suspension is separated from the ball milling beads, the suspension is dried to remove the dispersant, and then pre-calcined in a muffle furnace to obtain a precursor, wherein 0<x≤1; (3) mixing the precursor obtained in step (2) with 1-10% of LiTaO3 by weight of the precursor, and ball milling with isopropanol as a dispersant. After the ball milling, separating the suspension from the ball milling beads, drying the suspension to remove the dispersant, and obtaining a powder sample; (4) The powder sample obtained in step (3) is pressed into a tablet and subjected to a powder embedding treatment, and then transferred to a muffle furnace for sintering. The rough sample is taken out and polished on both sides to obtain the lithium lanthanum zirconium tantalum oxide solid electrolyte ceramic sheet with a lithium tantalate composite garnet structure.

[0007] Furthermore, in step (1), the heating treatment temperature is 700-950° C., and the heating treatment time is 5-18 h; Furthermore, in step (2), the lithium hydroxide monohydrate is fed in excess; Furthermore, in step (2), an agate ball mill is used, and the ball-to-material mass ratio is 2-5:1; the agate ball mill is placed in a planetary ball mill, the speed of the ball mill is 300-500 rpm, and the ball milling time is 5-36 h; Furthermore, in step (2), the pre-firing temperature is 800-950°C, the heating rate during pre-firing is 1-5°C / min, and the pre-firing time is 3-12 h; Furthermore, in step (3), an agate ball mill is used, and the ball mass to material ratio is 2-5:1; the agate ball mill is placed in a planetary ball mill, the ball mill speed is 300-500 rpm, and the ball milling time is 5-36 h; Furthermore, in step (4), the tableting pressure is 100-600 MPa, and the holding time is 5-15 min; Furthermore, the powder embedding material in step (4) is the same as the powder sample used for tableting; Furthermore, in step (4), the sintering temperature is 1100-1300°C, the heating rate during sintering is 1-5°C / min, and the sintering time is 2-24 h; Furthermore, in step (4), the polishing method is hand polishing using SiC sandpaper, and the thickness of the solid electrolyte ceramic sheet after polishing is 0.5-2 mm.

[0008] EIS test: Conductive silver paste was applied on both sides of the prepared solid electrolyte, and it was used as a lithium ion blocking electrode after drying at 120°C. The test frequency range was 10 MHz~10 Hz, and the voltage amplitude was 100 mV. The test temperatures were room temperature 23°C, 60°C, 90°C, 120°C, 150°C and 180°C, respectively. The Arrhenius curve was obtained using the Arrhenius formula, and the activation energy of ion migration was calculated.

[0009] The lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure described in the present invention is prepared by the above method. The lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure prepared by the present invention can be applied to all-solid-state lithium ion batteries. Specifically, lithium lanthanum zirconium tantalum oxide with a lithium tantalate composite garnet structure is used as an electrolyte material, and a button-type all-solid-state lithium ion battery is assembled with a positive electrode active material and a lithium metal negative electrode. The lithium lanthanum zirconium tantalum oxide solid electrolyte prepared by the present invention has stability to a variety of electrode materials, so it can be used to form a battery with a variety of electrode materials. Preferably, the positive electrode active material includes at least one group of lithium cobalt oxide, lithium iron phosphate, nickel cobalt manganese ternary and lithium-rich manganese-based positive electrode materials. Preferably, the lithium metal negative electrode is a pure lithium sheet with a thickness of 0.05-0.3 mm. Preferably, a current collector with a thickness of 0.2-0.5 mm is used as a conductive buffer layer of the negative electrode, and the current collector is one or more of nickel foam, carbon fiber, and foil (stainless steel, aluminum, copper, nickel, platinum, etc.). According to the order of "positive electrode shell / positive electrode active material / lithium lanthanum zirconium tantalum oxide as electrolyte / lithium metal negative electrode / stainless steel gasket / current collector / negative electrode shell", the button battery is pressurized and packaged. Preferably, the button battery specification is one of CR2032 (diameter 20mm, thickness 3.2mm) and CR2025 (diameter 20mm, thickness 2.5mm), the national standard number is GB / T 8897.3-2021, and the packaging pressure is 1~10 MPa. Through the composite of lithium tantalate, the density and ion conductivity of the solid electrolyte are improved, the growth of lithium dendrites is suppressed, and the prepared all-solid-state lithium-ion battery has good cycle stability.

[0010] Compared with the prior art, the outstanding features and beneficial effects of the present invention are: 1. The present invention proposes a new method for preparing a composite solid electrolyte by adding lithium tantalate at the grain boundary of the solid electrolyte; 2. In the composite garnet structure lithium lanthanum zirconium tantalum oxide solid electrolyte proposed by the present invention, lithium tantalate is aggregated at the grain boundary, which enhances the bonding strength of the grain boundary, reduces the porosity and thus improves the density; 3. The lithium tantalate described in the present invention will not react with the garnet structure solid electrolyte, and will not generate impurities that hinder ion transmission, thereby improving the ion conductivity at room temperature, reducing the migration activation barrier of lithium ions, and effectively solving the problem of low total ion conductivity caused by grain boundary problems; 4. The lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure described in the present invention has a simple preparation process and its advantages of improving density and ion conductivity can be used as an ideal solid electrolyte material in all-solid-state lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 X-ray diffraction patterns of the composite solid electrolytes prepared in Example 1 and Comparative Example 1 of the present invention; Figure 2 The SEM images of the cross sections of the composite solid electrolytes prepared in Example 1 and Comparative Example 1 of the present invention; Wherein Figure (a) corresponds to the SEM image of the cross section of the composite solid electrolyte prepared in Example 1, and Figure (b) corresponds to the SEM image of the cross section of the composite solid electrolyte prepared in Example 1; Figure 3 The AC impedance spectra of the composite solid electrolytes prepared in Example 1 and Comparative Example 1 of the present invention at room temperature; Figure 4 The composite solid electrolyte prepared in Example 1 and Comparative Example 1 of the present invention is a variable temperature AC impedance spectrum; wherein Figure (a) corresponds to the variable temperature AC impedance spectrum of the composite solid electrolyte prepared in Example 1, and Figure (b) corresponds to the variable temperature AC impedance spectrum of the composite solid electrolyte prepared in Comparative Example 1; Figure 5 for Figure 4 The activation energy curve of lithium ion migration calculated from the variable temperature AC impedance data shown. DETAILED DESCRIPTION

[0012] Embodiment 1: Composite 3 wt% LiTaO3-Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte (1) Place lanthanum oxide in a muffle furnace and heat it at 900°C for 12 h. (2) 2.759 g of lithium hydroxide monohydrate, 7.331 g of heat-treated lanthanum oxide, 2.588 g of zirconium oxide and 1.988 g of tantalum oxide were mixed and placed in an agate ball mill with a ball-to-material mass ratio of 3:1. 40 mL of isopropanol was added as a dispersant. The agate ball mill was placed in a planetary ball mill for ball milling at a speed of 350 rpm for 12 h. After the ball milling, the suspension was separated from the ball mill beads, dried in an oven at 80 °C, and then pre-calcined in a muffle furnace at 900 °C for 5 h to obtain 13.3 g of precursor Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Solid electrolyte powder, heating rate is 5℃ / min; (3) The precursor obtained in step (2) was mixed with 0.399 g of LiTaO3 and placed in an agate ball mill with a ball-to-material mass ratio of 3:1. 40 mL of isopropanol was added as a dispersant. The agate ball mill was placed in a planetary ball mill for ball milling. The ball mill speed was 350 rpm and the ball milling time was 12 h. After the ball milling was completed, the suspension was separated from the ball mill beads and dried in an oven at 80 °C to obtain 13.5 g of a powder sample. (4) 1.5 g of the powder sample obtained in step (3) was kept at a pressure of 400 MPa for 10 min to obtain a composite solid electrolyte sample blank. The blank was buried with the same powder and then sintered at 1150°C in a muffle furnace for 2 h. The surfaces of both sides of the obtained sample blank were polished with 400 mesh, 2000 mesh, and 5000 mesh SiC sandpaper in sequence to obtain a composite solid electrolyte ceramic sheet with a thickness of 1.8 mm. The heating rate was 5°C / min.

[0013] The composite solid electrolyte ceramic sheet obtained above was subjected to XRD test, and the results are as follows: Figure 1 As shown, it can be seen that compared with the standard card (PDF#80-0457), the obtained composite solid electrolyte ceramic sheet phase is a pure cubic phase, and a small LiTaO3 peak appears at around 23.7°.

[0014] The SEM test results of the composite solid electrolyte ceramic fragment obtained above are as follows: Figure 2 As shown in (a), it can be seen that the sample has uniform grain size, the grains are tightly combined, the grain boundaries are unclear, the pores are few, and the calculated density is 96.7%.

[0015] The EIS test of the composite solid electrolyte ceramic sheet obtained above was carried out, and the results are as follows Figure 3 As shown. The basic principle of measuring conductivity by impedance method is that when current passes through a conductor, it will be hindered by the electrons and ions inside the conductor, thereby generating resistance or impedance. According to Ohm's law, R=V / I, where R is resistance, V is voltage, and I is current. Resistivity ρ=RS / L, L is length, and S is cross-sectional area. The relationship between conductivity and resistivity is σ=1 / ρ. Using ZView software fitting, the optimal equivalent circuit diagram was selected to fit the EIS data (Energy Storage Materials 2019. 22. 207–217). The ionic conductivity is obtained according to the slope of the oblique line in the low-frequency region of the fitting result. It can be seen from the figure that the conductivity of the prepared sample is 7.08×10 -4 S cm -1 At the same time, the variable temperature EIS was tested, and the results are as follows Figure 4 As shown in (a) in the figure. And according to Figure 4The impedance and temperature obtained are combined with the Arrhenius formula ,get Figure 5 Arrhenius curve in which σ is conductivity, T is temperature, E a is the activation energy, R is the molar gas constant, and A is the pre-exponential factor. The two sets of data were linearly fitted using the origin software according to the linear regression equation (J. Korean Phys. Soc. 2018. 73. 1535–1540). The formula shows that ln(σT) and 1 / T are linearly related, with a slope of -E a / R, so the activation energy E of the sample in Example 1 can be obtained based on the slope a is 0.286 eV.

[0016] Embodiment 2: Composite 1 wt% LiTaO3-Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte The other steps are the same as those in Example 1, except that the mass of the LiTaO3 powder weighed in step (3) is 0.133 g.

[0017] Embodiment 3: Composite 2 wt% LiTaO3-Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte The other steps are the same as those in Example 1, except that the mass of the LiTaO3 powder weighed in step (3) is 0.266 g.

[0018] Embodiment 4: Composite 5 wt% LiTaO3-Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte The other steps are the same as those in Example 1, except that the mass of the LiTaO3 powder weighed in step (3) is 0.665 g.

[0019] Embodiment 5: Composite 7 wt% LiTaO3-Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte The other steps are the same as those in Example 1, except that the mass of the LiTaO3 powder weighed in step (3) is 0.931 g.

[0020] Embodiment 6: Application of a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure in an all-solid-state lithium ion battery, specifically as follows: (1) The solid electrolyte prepared in Example 1 is selected as the electrolyte material of this example; (2) Selecting lithium iron phosphate as the positive electrode active material; (3) A pure lithium metal sheet with a thickness of 0.05 mm was selected as the negative electrode material, attached and pressed onto one side of the above electrolyte, and heated at 300 °C for 20 min to ensure a tight bond at the interface, and a 0.3 mm thick nickel foam was selected as the negative electrode current collector; (4) Assemble button cells under a pressure of 5 MPa according to the structure of positive electrode shell / positive electrode active material / solid electrolyte / lithium metal negative electrode / stainless steel gasket / current collector / negative electrode shell.

[0021] The battery cycle stability was tested using a LAND CT2001A charge and discharge instrument at current densities of 0.1, 0.2, and 0.4 mA, respectively. The experimental results showed that the composite solid electrolyte has good cycle stability.

[0022] Comparative Example 1: Composite 0 wt% LiTaO3-Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte (1) Place lanthanum oxide in a muffle furnace and heat it at 900°C for 12 h. (2) 2.759 g of lithium hydroxide monohydrate, 7.331 g of heat-treated lanthanum oxide, 2.588 g of zirconium oxide and 1.988 g of tantalum oxide were mixed and placed in an agate ball mill with a ball-to-material mass ratio of 3:1. 40 mL of isopropanol was added as a dispersant. The agate ball mill was placed in a planetary ball mill for ball milling at a speed of 350 rpm for 12 h. After the ball milling, the suspension was separated from the ball mill beads, dried in an oven at 80 °C, and then pre-calcined in a muffle furnace at 900 °C for 5 h to obtain 13.3 g of precursor Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Solid electrolyte powder, heating rate is 5℃ / min; (3) The precursor obtained in step (2) was placed in an agate ball mill with a ball-to-material mass ratio of 3:1. 40 mL of isopropanol was added as a dispersant. The agate ball mill was placed in a planetary ball mill for ball milling. The ball mill speed was 350 rpm and the ball milling time was 12 h. After the ball milling was completed, the suspension was separated from the ball mill beads and dried in an oven at 80°C to obtain 13.1 g of a powder sample. (4) 1.5 g of the powder sample obtained in step (3) was kept at a pressure of 400 MPa for 10 min to obtain a composite solid electrolyte sample blank. The blank was buried with the same powder and then sintered at 1150°C in a muffle furnace for 2 h. The obtained sample blank was polished with 400 mesh, 2000 mesh, and 5000 mesh SiC sandpaper in sequence to obtain a solid electrolyte ceramic sheet with a thickness of 1.8 mm. The heating rate was 5°C / min.

[0023] The solid electrolyte ceramic sheet obtained above was subjected to XRD test, and the results are as follows: Figure 1 As shown, it can be seen that compared with the standard card (PDF#80-0457), the obtained solid electrolyte ceramic sheet phase is a pure cubic phase.

[0024] The SEM test results of the solid electrolyte ceramic fragment obtained above are as follows: Figure 2 As shown in (b), it can be seen that the sample has uniform grain size, loose grain bonding, clear grain boundaries, and more pores. The calculated density is 89.2%.

[0025] The solid electrolyte ceramic sheet obtained above was subjected to EIS test, and the results are as follows: Figure 3 As shown, the basic principle of measuring conductivity by impedance method is that when current passes through a conductor, it will be hindered by the electrons and ions inside the conductor, thereby generating resistance or impedance. According to Ohm's law, R=V / I, where R is resistance, V is voltage, and I is current. Resistivity ρ=RS / L, L is length, and S is cross-sectional area. The relationship between conductivity and resistivity is σ=1 / ρ. Using ZView software fitting, the optimal equivalent circuit diagram was selected to fit the EIS data (Energy Storage Materials 2019. 22. 207–217). The ionic conductivity is obtained based on the slope of the oblique line in the low-frequency region of the fitting result. It can be seen from the figure that the conductivity of the prepared sample is 4.25×10 -4 S cm -1 At the same time, the variable temperature EIS was tested, and the results are as follows Figure 4 As shown in (b) in the figure. And according to Figure 4 The impedance and temperature obtained are combined with the Arrhenius formula ,get Figure 5Arrhenius curve in which σ is conductivity, T is temperature, E a is the activation energy, R is the molar gas constant, and A is the pre-exponential factor. The two sets of data were linearly fitted using the origin software according to the linear regression equation (J. Korean Phys. Soc. 2018. 73. 1535–1540). The formula shows that ln(σT) and 1 / T are linearly related, with a slope of -E a / R, so the activation energy E of the sample in comparative example 1 can be obtained according to the slope a is 0.300 eV.

[0026] Comparative Example 2: Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 Preparation of solid electrolyte The other steps are the same as those in Comparative Example 1, except that in step (4), the sintering temperature is 1250° C. and the sintering time is 12 h.

[0027] In summary, the present invention provides a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure. From the solid electrolyte test results obtained in the embodiments and comparative examples, it is not difficult to see that the present invention can fill the pores at the grain boundaries of the composite solid electrolyte by introducing the additive LiTaO3, which is beneficial to reduce the sintering temperature and sintering time and reduce the total resistance, thereby obtaining higher density, higher ionic conductivity and lower activation energy.

[0028] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, are preferred embodiments of the present invention, and do not constitute limitations on the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the claims attached to the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the attached claims, or the equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure, characterized in that: The steps are as follows: (1) placing lanthanum oxide in a muffle furnace and heating it to remove impurities to obtain pure lanthanum oxide powder; (2) lithium hydroxide monohydrate, lanthanum oxide, zirconium oxide and tantalum oxide heat-treated in step (1) are mixed according to the chemical formula Li 7- x LqCy 2-x Ta x O 12 The mixture is mixed in a molar ratio of 100 and 100 and put into a ball mill, and ball milling is performed using isopropanol as a dispersant. After the ball milling is completed, the suspension is separated from the ball milling beads, the suspension is dried to remove the dispersant, and then pre-calcined in a muffle furnace to obtain a precursor, wherein 0<x≤1; (3) mixing the precursor obtained in step (2) with 1-10% of LiTaO3 by weight of the precursor, and ball milling with isopropanol as a dispersant. After the ball milling, separating the suspension from the ball milling beads, drying the suspension to remove the dispersant, and obtaining a powder sample; (4) The powder sample obtained in step (3) is pressed into a tablet and subjected to a powder embedding treatment, and then transferred to a muffle furnace for sintering. The rough sample is taken out and polished on both sides to obtain the lithium lanthanum zirconium tantalum oxide solid electrolyte ceramic sheet with a lithium tantalate composite garnet structure.

2. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: In step (1), the heating treatment temperature is 700-950°C and the heating treatment time is 5-18 h.

3. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: In step (2), the amount of lithium hydroxide monohydrate added is excessive.

4. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: In step (2) and step (3), an agate ball mill is used, and the ball-to-material mass ratio is 2-5:1; the agate ball mill is placed in a planetary ball mill, the rotation speed of the ball mill is 300-500 rpm, and the ball milling time is 5-36 h.

5. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: The pre-firing temperature in step (2) is 800-950°C, the heating rate during pre-firing is 1-5°C / min, and the pre-firing time is 3-12 h.

6. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: In step (4), the tableting pressure is 100-600 MPa and the holding time is 5-15 min.

7. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: The embedding material in step (4) is the same as the powder sample used for tableting.

8. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: In step (4), the sintering temperature is 1100-1300°C, the heating rate during sintering is 1-5°C / min, and the sintering time is 2-24 h.

9. The method for preparing a lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure according to claim 1, characterized in that: The polishing method in step (4) is hand polishing using SiC sandpaper, and the thickness of the solid electrolyte ceramic sheet after polishing is 0.5~2 mm.

10. A lithium lanthanum zirconium tantalum oxide solid electrolyte with a lithium tantalate composite garnet structure, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Tantalum-doped cubic garnet structured Li7La3Zr&lt;2-x&gt;TaxO12 material synthesized via intermediate phase, and synthesis method thereof

    CN105336980A

  • Garnet type solid electrolyte capable of effectively inhibiting lithium dendrites and preparation method of garnet type solid electrolyte

    CN114243004A

  • Solid electrolyte with lithium-loving surface and preparation method thereof

    CN115763955A

  • Method for accurately preparing cubic system lithium-rich garnet structure solid electrolyte

    CN116525962A

  • Garnet-lithium titanate composite electrolyte

    US20210347697A1